Implementation of Double Track Program Policy in High School Based on East Java Governor Regulation No. 139 of 2018 - Ul Jannah, Zumrotun Nisaa; Saleh, Choirul; Hayat, Ainul (LP. Ma'arif Janggan Magetan, 2025)
The Double Track Programme is a strategic policy made by the East Java Provincial Government which has been outlined through East Java Governor Regulation No. 139/2018 concerning improving the skills of high school students which aims to prepare students who do not continue their studies in order to increase the competitiveness of high school graduates armed with vocational skills to be able to enter the world of work. The scope of this implementation is adjusted in article 3. This research uses descriptive qualitative research by collecting data through observation, interviews, and documentation. This research involved 9 informants, namely teacher trainers, facilitators, students and the location of this research was carried out at SMAN 1 Montong, Tuban Regency, which has less than 50% of students who continue their studies. The results of this study reveal that the Double Track programme that has been implemented at SMAN 1 Montong also focuses on improving the hard skills and soft skills of students by collaborating the learning process of critical thinking, communication, and cooperation so that students can have the opportunity to work armed with their competencies. Through the double track programme in the future there will be more cooperation with DUDI and as a form of distribution after graduation to work according to the skills that have been learned.